Finger millet porridges subjected to different processing conditions showed low glycemic index and variable efficacy on plasma antioxidant capacity of healthy adults - Kumari, Disna; Chandrasekara, Anoma; Athukorale, Prisko; Shahidi, Fereidoon (Food production, processing and nutrition, 2020)
Finger millet porridges (FMP), rich in nutrient and non-nutrient compounds have been used in the traditional food cultures in Asia. The aims of the study were to determine the effect of different processing conditions of finger millet grains on glycemic response, phenolic content and the antioxidant activities of FMP and to determine the short term and long term efficacy of its consumption on plasma antioxidant levels of healthy adults. Twelve types of FMP were prepared combining different processing conditions. Phenolic content of porridges as well as antioxidant activities were determined. The glycemic index (GI) and glycemic load (GL) values of FMP were also evaluated. The long term efficacy of FMP consumption on plasma glucose (PG), total cholesterol (TC) levels and plasma antioxidant capacity (PAC) of 18 subjects were investigated using a 24 weeks randomized cross-over study. The short term efficacy of porridge consumption on AC was determined. PAC was measured by trolox equivalent antioxidant capacity (TEAC) and ferric ion reducing antioxidant power (FRAP). All FMP exhibited low GI values (< 55) except the raw roasted flour which showed high and medium GI values for both particle sizes used. Parboiling of finger millet grains with 15 min steaming produced FMP with low glycemic response and possessed high PAC. Compared to baseline, PAC measured using FRAP and TEAC assays increased after 8 weeks consumption of porridge though significant changes were not observed for PG and TC levels. Furthermore, PAC was increased by 23 and 14% after 2 h of porridge consumption as measured by TEAC and FRAP, respectively. FMP consumption increased the plasma total antioxidant capacity of healthy adults. Further research on examining the potential of FMP on improving the antioxidant capacity in patients with diabetes is warranted. Graphical abstract